Clinical Significance of Salivary CD44sol Levels in Laryngeal Carcinomas. (2nd September 2014) - Trapasso, Serena; Aragona, Teodoro; Franco, Teresa; Allegra, Eugenia
Abstract : Objectives: Describe our results about the clinical significance of salivary CD44sol levels in laryngeal carcinomas and analyze its emerging role as a diagnostic and prognostic factor. Methods: The study design was prospective. Patients with laryngeal cancer were selected and recruited at the Division of Otolaryngology, University of Catanzaro, from January to December 2012. Patients with benign head and neck disease were also included as a control group. For each patient, clinical‐anamnestic data were collected in a database. The data were recorded relating to any disease recurrence and locoregional or distant metastases detected during the follow‐up, every 3 months. The sampling of undiluted saliva was performed the day before surgery and during the follow‐up, every 3 months. Salivary CD44sol levels were determined using the enzyme‐linked immunosorbent assay method. Results: In patients with laryngeal carcinoma, salivary CD44sol levels were significantly higher than those in the control group ( P <. 001). There is significant reduction in salivary CD44sol levels observed during the follow‐up at 3 and 6 months ( P <. 04 and P <. 0002, respectively) when compared with those at the time of diagnosis of laryngeal cancer. Conclusions: In a previous study, we demonstrated that CD44sol can be an effective biological marker with useful application for early detection and screening in laryngeal cancer. The analysis of the obtained data shows that the Elisa CD44sol determination can represent a promising prognostic test.